School, market work, and household chores: A day of Guatemalan children - Carla Canelas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper utilizes a unique dataset on time use to study the determinants of the number of hours allocated to market work, household chores, and school related activities of Guatemalan children between 2000 and 2011. The paper also exploits information on the duration of schooling in order to compute survival probabilities or the probability of dropping out of school conditional on having stayed in school for time t. Results suggest that working children are two to four times more likely to drop out of school or to have never enrolled than the rest of the children in the sample. The findings also reveal the traditional gender specialization on market and domestic activities from early ages. While market work increases the likelihood of dropping out of school for both boys and girls, household chores add additional pressure to girls' time allocation and further increase school failure.
Keywords: 330; child labour; school attainment; Guatemala